The Relationship Between Research & Development Expenditures and Economic Growth: Panel Data Analysis - Ozcan, Burcu; Ari, Ayse (Maliye Bakanligi, 2014)
Research and development activity (R&D) as an impulsive force of economic growth has a leading role in the economic structures of countries. The endonegous growth theories that have gained popularity since 1980s have highlighted the importance of R&D in the economic growth process. In this study, the relationship between R&D and economic growth is analyzed for the selected 15 OECD countries from 1990 to 2011 within the framework of panel data model. The results of whole panel set indicate that R&D affects economic growth positively. As a policy implication, countries aiming to accelerate the life standard and economic growth must emphasize R&D investments.
Keywords: R&D; Economic Growth; New Growth Theories; Panel Data Model